ANALISIS PENGARUH UKURAN KAP DAN TATA KELOLA PERUSAHAAN TERHADAP INTEGRITAS LAPORAN KEUANGAN (Studi Kasus Pada Perusahaan Sektor Properti dan Real Estate yang Terdaftar di BEI Periode 2013-2015) - Eman Sukanto; Widaryanti Widaryanti (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2018)
This study aims to obtain empirical evidence of the effect of KAP size and corporate governance (audit committees, independent commissioners, management ownership, institutional ownership) to the integrity of financial statements to property and real estate companies in Indonesia. The independent variables used in this study are KAP and corporate governance measures analyzed by audit committees, independent commissioners, management ownership, institutional ownership of the integrity of financial statements. The dependent variable used in this study is the integrity of the financial statements measured by using conservatism, in the year of observation from 2013-2015. The sample in this research is property and real estate company listed in Indonesia Stock Exchange (IDX) in period 2013-2015. The data collected by purposive sampling method. A total of 32 companies were determined as samples. The method of analysis of this study using logistic regression. The results of this study indicate that the size of KAP and institutional ownership have a significant effect on the integrity of financial statements. Meanwhile, audit committees, independent commissioners, management ownership have no significant effect on the integrity of financial statements